2006
DOI: 10.1590/s0102-311x2006000400013
|View full text |Cite
|
Sign up to set email alerts
|

The HIV/AIDS epidemic and changes in injecting drug use in Buenos Aires, Argentina

Abstract: This article discusses the changes in injecting drug use from 1998 to 2003 in Buenos Aires, Argentina. The Rapid Situation Assessment and Response methodology was used to obtain the information. Quantitative and qualitative techniques were triangulated: 140 current IDUs and 35 sex partners of injection drug users (IDUs) were surveyed; 17 in-depth interviews with the surveyed IDUs and 2 focus groups were held, as well as ethnographic observations. The way in which risk and care practices among injecting drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…A high risk for HIV infection has previously been observed in this group of individuals. [8,[13][14][15][16] In Buenos Aires, a previous study demonstrated that the prevalence of HIV among IDU was 44.3% in 2001. [8] As IDU was formerly the most common mode of transmission in Argentina, it is expected that individuals belonging to this group would have been infected for a longer period of time compared with other more recently prevalent modes of transmission, such as heterosexual contact.…”
Section: Discussionmentioning
confidence: 99%
“…A high risk for HIV infection has previously been observed in this group of individuals. [8,[13][14][15][16] In Buenos Aires, a previous study demonstrated that the prevalence of HIV among IDU was 44.3% in 2001. [8] As IDU was formerly the most common mode of transmission in Argentina, it is expected that individuals belonging to this group would have been infected for a longer period of time compared with other more recently prevalent modes of transmission, such as heterosexual contact.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while AIDS mortality rates overall started to decline in Argentina after 1996, the same trend has not been observed among injecting drug users, who have experienced large numbers of deaths in recent years. This suggests that injecting drug users have not benefited sufficiently from the country's antiretroviral treatment programme (Rossi et al, 2006 (National AIDS Programme Uruguay, 2006). Nevertheless, infection levels are high among certain groups in the capital, Montevideo, where the epidemic is concentrated: 22% among men who have sex with men (Montano et al, 2005), 19% among injecting drug users and 10% among non-injecting drug users (Vignoles et al, 2006).…”
Section: Brazil's Dual Emphasis On Prevention and Treatment Has Helpementioning
confidence: 99%
“…Most studies on the prevalence of infections that are either bloodborne or sexually acquired among drug users in Argentina have been conducted among injecting drug users (IDU), over 95% of whom inject cocaine. Several studies have demonstrated a high seroprevalence of human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) 2,3,4,5 among the drug-injecting population. Cocaine, which was regarded several decades ago as a drug consumed exclusively by affluent people, has now extended into low-income sectors that were formerly far from its reach.…”
Section: Introductionmentioning
confidence: 99%